Human bocavirus and human metapneumovirus in children with lower respiratory tract infections: Effects on clinical, microbiological features and disease severity . Issue 1 (26th May 2022) - Ademhan Tural, Dilber; Yalcin, Ebru; Emiralioglu, Nagehan; Ozsezen, Beste; Alp, Alpaslan; Sunman, Birce; Gozmen, Onur; Dogru, Deniz; Ozcelik, Ugur; Kiper, Nural
Abstract: Background: We aimed to compare the clinical findings of human bocavirus (HBoV) and human metapneumovirus (HMPV) infections, and to analyze the effects of coinfections on clinical features and disease severity in children with HBoV and HMPV infections. Methods: Data were collected from 125 children with lower respiratory tract infections due to HBoV or HMPV, detected from nasal swap by real‐time polymerase chain reaction (PCR) during the period from January, 2013 to December, 2017. In total, there were 101 HBoV (group 1) and 23 HMPV (group 2) infections in our data. The patients were further divided into four subgroups according to the coinfection status: HoBV only (subgroup 1, n = 41), HMPV only (subgroup 2, n = 19), HBoV and coinfection with other respiratory viruses (subgroup 3, n = 60), and HMPV and coinfection with other respiratory viruses (subgroup 4, n = 4). Results: The majority (88.8%) of the patients were aged 5 years or younger. Coinfections with other respiratory viruses were significantly more common in group 1 ( P = 0.001). Among patients who had nosocomial pneumonia, patients with HBoV infections had significantly longer mean length of hospital stay (LOS) than those with HMPV infections ( P = 0.032). The hospitalization and antibiotic requirements were significantly higher in subgroup 1 than subgroup 3 ( P = 0.005, 0.039, resp.) According to the logistic regression analyses, the LOS increased by 21.7 times with HBoV infections ( P = 0.006). Conclusions: Human bocavirus and HMPV infections are serious pathogens mostly seen in children and usually requiring hospitalization regardless of co‐infection status. The HBoV infections caused longer LOS than the HMPV infections in patients with nosocomial infections.